The use of HBIM in the modeling of the Solar da Beira building in Belém/PA for digital registration (Research, Society and Development, 2022)
Building information modeling (BIM) is a modeling technology applied in the Architecture, Engineering and Construction (AEC) industry. It refers to a representative three-dimensional modeling program that includes a set of technologies and actions that allow managing the life cycle of a building. HBIM, on the other hand, which is an extension of the BIM concept applied to existing buildings, mainly historic ones, aiming to document, analyze and preserve these constructions. However, in Brazil there are many historic buildings without records in the BIM libraries, in other words, they do not have information about their construction or changes carried out over the years. This work aims to perform the modeling of the Solar da Beira building, located in Belém do Pará, in order to describe and discuss the procedures adopted and analyze the facilities and difficulties encountered during the process. As well as, emphasize and understand the importance of using HBIM in historic buildings. The method was based on literature review, technical inspections and data collection through floor plans and sections that were subjected to modeling. Thus, it was possible to record the construction data of the building and make them available so that studies of this building and possible future interventions and preservation are facilitated.